Personal taxes and the time variation of stock returns – evidence from the UK - Brealey, Richard A.; Kwan, Sabrina (Journal of Banking & Finance, 1999)
A potential explanation for the time-series predictability of market returns with dividend yields is the differential tax treatment of capital gains and dividends. This article investigates to what extent the predictability of long-horizon returns can be explained by this tax effect. Assuming that after-tax expected returns are constant, we test the derived relationships between pretax returns and lagged dividend yields with UK data. We also compare the predictability of before-tax long-horizon returns with that of after-tax returns. The results indicate that the tax treatment of dividends does not significantly contribute towards the predictability of stock returns.